Evaluation of energy flow, dissipation and performances for advanced adsorption assisted heat transformation systems : temperature-entropy frameworks - Han, Bo (2021)
This article presents the entropy flow and generation of an adsorption assisted heat transformation (A-HT) system. Hence the Gibbs analogy and the thermodynamic property fields of adsorbents + water systems are employed to formulate the entropy balance of adsorption beds. Later, the experimentally confirmed isotherms, kinetics and bed heat exchanger data are applied for computing the energetic performances of adsorption system in terms of entropy flow and generation, from which one can calculate (i) the system-performances with respect to heating and cooling capacities, specific water production and the overall efficiency and (ii) dissipations from each component of A-HT systems. The temperature entropy-flow (T-Sf) maps show close loops for the evaporator, the condenser and the beds indicating the stored energy under batch operating conditions of A-HT cycle. It is observed that the entropy generation (Sg) are mainly contributed by various processes such as mass and heat transfer, de-superheating and flushing of heat transfer fluids. The highest entropy generation occurs in the adsorption bed during desorption period, and the least Si is found in the evaporator. The proposed temperature-entropy maps can be applied to design each component of bed heat exchanger with minimum entropy generation. It is found that the entropy flow and generation depend on the periods of batch operation, the heating source temperature, and the quality of porous adsorbents.